MULHERES MPA-PR LUTAS, FORMAÇÃO E CONSTRUÇÃO DE IDENTIDADES - MÜLLER, ADRIANA CRISTINA (2020)
This research addresses the relationship between the training processes carried out in the SFM and the change in world reading, empowerment and liberation of four militant peasant women leaders of the SFM-PR. How does it propose to research how the life stories of the women of the Small Farmers' Movement of the state of Paraná (henceforth SFM -PR) and the formative processes lived in the struggle and formation in the movement contributed to their constitution as militant and woman in a popular social movement? As a general objective we point out: to analyze the life stories of the women leaders of the SFM /PR and the formative processes lived by them inside and outside the movement and their constitution as militant and woman in a social movement; and as specific objectives: to research the historical panorama of the SFM /PR in the general scope of the peasant struggles in Brazil; to analyze the contents and methodologies used in the formation processes carried out by the SFM /PR; to verify through interviews how the participation of women in the constitution of the SFM /PR occurred, as well as their constitution as militant and woman in a social movement. To carry out this research work, of qualitative approach, we use as methodological procedures the bibliographical, documentary and field research (semi-structured interviews).As categories of analysis we score: work, gender, social sex relations, peasantry and social movements. The theoretical exposition is organized in three chapters. In the first chapter, entitled "The struggle of the people makes a new time emerge" in which we approach the historical process of the emergence and performance of SFM Brazil and SFM Paraná and the insertion of women in this context, dialoguing with elements that configure the relevance of this participation, regarding changes in power relations, gender and sex. In the second chapter, entitled "Praxis as a formative element" in which we present the process of historical research carried out by the SFM in order to understand the origin of peasantry, which culminated in significant theoretical production with the publication of several books and the elaboration of the Peasant Plan (2003) a Social and Popular Project for the countryside.The understanding of the Plan of Formation and the formative intention of the Movement, an emancipatory perspective of the construction of working class and peasant consciences, of class identities and class affirmation. In the third chapter, entitled "Militancy and life in the popular social movement, exemplary stories" in which we approach some more elements of the social relations of power, gender and sex, focusing on their unfolding in the countryside, in peasant reality. We brought to light, from the interviews, aspects of the militancy of four peasant women leaders of the SFM -PR and the meaning of the formation carried out by the Movement, in its broad understanding, in their life and reading of their world. While this simple study explained the relevance of the formation carried out by the popular social movements, especially the SFM, object of this research, and the widening of class consciousness, constitution of identities, empowerment and liberation of militant women and men.